Higher education and economic growth: A longitudinal study of European regions 2000–2017. (June 2022) - Agasisti, Tommaso; Bertoletti, Alice
Abstract: This paper investigates the impact of regional higher education systems (HESs) on economic growth, based upon 284 European regions (NUTS 2) over an 18-year period (from 2000 to 2017). The empirical framework specifically models the heterogeneity of the HESs by including indicators on university concentration, on the size of the HES and on HES performance and other important factors. The analysis is based on a novel and integrated dataset, created by collecting and combining indicators from different data sources (Eurostat, OECD, WHED and InCites). The results reveal that an increase in number of universities in a region is conducive to stronger economic growth within that region. The quality of research and a specialisation in STEM subjects are the primary drivers through which universities impact positively on the regions' economic development. Highlights: The increase in the number of universities in a region is conducive to its stronger economic growth. The effect is two times larger if the size of the higher education system is considered. The quality of research activities is an important driver for the growth in the GDP per capita of the region. There is a stronger effect for universities specialised in STEM disciplines. No significant effects associated with the type of universities funding (i.e. public vs private).